Comparative analysis of neural network Models for peripheral blood cell image classification - Mollah, Md Tanzid; Shahriar, Mahi; Fahim, Mohammad; Ahmed, Zehan; Sakib, Kaji Sadman (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.